PHILOSOPHY OF POETRY: NOTHINGNESS/NOT-BEING AS A PHILOSOPIC CATEGORY IN MALLARME AND SHOPOV (Philological Studies, 2023)
The study problematizes some questions of the philosophy of poetry, a new sub-discipline in the hermeneutic-phenomenological exploring of poetic texts, which has a philosophical background. In this case, we have focused on the relations between philosophers and their poets, Sartre and Mallarme in French literature, and Stardelov and Shopov in Macedonian literature. Subsequently, we try to compare two philosophical terms in their work and draw some parallels, not only between the philosophers and authors but also to their poetics.